2007
DOI: 10.1097/qad.0b013e32810fd72e
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drug resistance, HIV-1 tropism, and HIV-1 subtype among men who have sex with men with recent HIV-1 infection

Abstract: Antiretroviral drug resistance is relatively common among recently infected men who have sex with men in the United States. CXCR4-using strains were detected in a small number of these infections, which were all subtype B HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 18 publications
2
36
4
Order By: Relevance
“…Recent studies have found the frequency of X4/DM dualtropic strains in plasma samples from recently infected patients in the United States and Spain to be from 3.2% to 17.5% (14,15,16). Similarly, we found 15.9% (95% confidence interval…”
supporting
confidence: 72%
“…Recent studies have found the frequency of X4/DM dualtropic strains in plasma samples from recently infected patients in the United States and Spain to be from 3.2% to 17.5% (14,15,16). Similarly, we found 15.9% (95% confidence interval…”
supporting
confidence: 72%
“…In particular, in drug-naive MSM individuals, resistance (3.9%) is lower than that observed in other studies performed on the same risk class [52][53][54] and in other studies performed on heterogeneous risk classes. [55][56][57][58] The prevalence of resistance in antiretroviral-treated MSM individuals is around 60%, with a decreased trend over the years 2004-2006 (data not shown), in line with that observed in recent studies; 59,60 this diminished trend could explain the low prevalence of drug resistance in naive patients.…”
Section: Discussioncontrasting
confidence: 44%
“…Moreover, an additional patient with the R5 variant in plasma had the X4 strain in PBMCs. Recent studies have reported various frequencies of X4 dual/mixed (D/M) dualtropic strains (3.2 to 17.5%) in plasma samples from recently infected patients in the United States and Spain (13,19). A large French epidemiological study demonstrated that a high proportion of patients (62 of 390 patients [15.9%]) harbored X4 or dualtropic viruses in PBMCs at the time of primary infection, suggesting the existence of a cellular X4 viral reservoir that could persist for a lengthy period of time (21).…”
Section: Discussionmentioning
confidence: 99%